2010
DOI: 10.1063/1.3282682
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of energy band alignment and turn-on voltage in organic light emitting diodes

Abstract: Articles you may be interested inEfficiency dependence on alkali metal compound/Al bilayer cathode in organic light-emitting diodes Appl. Phys. Lett. 97, 223302 (2010); 10.1063/1.3522883Excimer-based red/near-infrared organic light-emitting diodes with very high quantum efficiency

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…12 The former only improved injection mechanism, while the latter has improved injection and transport characteristics afforded by diffusion into the transport layer. [12][13][14] These device performances conflict with our results. It is possible to assume that the Cs 2 CO 3 EIL reaction at the Al cathode is insufficient, due to the diffusion of Cs 2 CO 3 into the ETL.…”
contrasting
confidence: 99%
“…12 The former only improved injection mechanism, while the latter has improved injection and transport characteristics afforded by diffusion into the transport layer. [12][13][14] These device performances conflict with our results. It is possible to assume that the Cs 2 CO 3 EIL reaction at the Al cathode is insufficient, due to the diffusion of Cs 2 CO 3 into the ETL.…”
contrasting
confidence: 99%
“…Though, 3d and 3e have similar LUMO energy levels the HOMO is showing small difference. Wu and co-workers 47 showed that the turn-on voltage is mainly dependent on the HOMO and LUMO energies of the constituent layers. However, while using the HOMO and LUMO values to rationalize the differences in electroluminescence performances care must be exercised.…”
Section: Electroluminescence Characteristicsmentioning
confidence: 99%
“…The energy level alignment at organic and molecular semiconductor heterojunctions is generally recognized to be essential for the function and performance of organic electroluminescent 1,2 and photovoltaic devices. 3,4 Because of its direct relevance for understanding the underlying fundamental mechanisms, such as charge carrier recombination and generation, [5][6][7] the energy level alignment at these interfaces has been extensively studied by ultraviolet and X-ray photoelectron spectroscopy (UPS and XPS, respectively).…”
mentioning
confidence: 99%